The problems of provisions`s implementation of «the disabled the rights`s Convention» in the Republic of Kazakhstan (International relations and international law Journal, 2018)
The article consider the legal status of persons with disabilities in the Republic of Kazakhstan. Raises issues about the implementation of the Convention on the Rights of Persons with Disabilities, ratified by the Republic of Kazakhstan. Today, problems of the persons with disabilities are the one of the unsolved problems and it requires the society the cohesion and development, the integration of social groups, empowerment and equal rights of its citizens. Social and legal protection of invalids is RK social policy priority, and its main task – the humanization of all spheres of life of these people. The international community has only recently turned its attention to the protection of disabled rights. By the end of the 70s it was dominated by the concept of the fundamental rights recognition of all persons with disabilities without any special protective measures. However, the study of disability issues and the practical action to protect the rights of persons with disabilities have identified the need to create a separate system of international protection of their rights.Key words: disabled, disability, equal rights, social protection, rights of disabled.